Clinical and histological comparison of ulcerated lichen planus and chronic cutaneous lupus erythematosus: Aseries of six cases - Meenakshi Batrani; Asha Kubba; Raj Kubba; Kapil Chandra; Krishnakumar Subramanian (Wolters Kluwer Medknow Publications, 2016)
Cutaneous ulceration as the primary manifestation of chronic cutaneous lupus erythematosus (CCLE) and lichen planus (LP) is uncommon. In the absence of typical lesions, clinical diagnosis is challenging. We report six cases, three each of, CCLE and LP that presented with cutaneous ulcers. A detailed comparison of clinical and histopathological features between two groups was conducted. The statistical significance of comparative features could not be assessed because of small number of cases. In view of clinical and histopathological overlap, diagnosis requires clinico-pathological correlation and ancillary tests including direct immunofluorescence and antinuclear antibodies.